Physiological and psychological adaptations of trained cyclists to spring cycling camps - Dionne, J.-F.; Lajoie, C.; Gendron, P.; Freiberger, E.; Trudeau, F. (Journal of Human Kinetics, 2018)
The purpose of our study was to assess physiological adaptations and measure mood outcomes following a cycling training camp in competitive athletes. Fourteen competitive athletes (8 males, 6 females) performed 2 incremental tests to exhaustion before and after a training camp. Volume and intensity (load) of the training regimen were recorded. Submaximal and maximal metabolic data were analysed, as well as economy variables (gross mechanical efficiency and cycling economy). Skeletal muscle adaptations were assessed using near infrared spectroscopy (NIRS). For both genders (n = 14), peak power output, peak power output-W/kg ratio and peak power output-B[La] were significantly increased (p < 0.05) after the cycling training camp (p < 0.05). Significant increases occurred for gross mechanical efficiency measured at the lactate threshold (+4.9%) and at the same precamp lactate threshold power output (+2.9%). At the lactate threshold and Post Camp Lactate Threshold Power, cycling economy increased by 5.2 and 2.9%, respectively (p < 0.05). These power measurements were significantly correlated with individual fluctuations in deoxyhaemoglobin in the vastus lateralis for male cyclists only. Profile of Mood State questionnaire results showed that subcategories "Tension-Anxiety", "Confusion", "Fatigue" and "Total Global Score" significantly decreased after the training camp. Cycling training camps were associated with positive adaptations (increased cycling economy, gross mechanical efficiency and power output) as well as some mental benefits. This indicates that despite some significant physiological adaptations participants probably did not overreach during their CTC.